Assessment of medical errors awareness among nursing students during their clinical internship: Palestinian perspectives - Basma Salameh; Sameer A. Alkubati; Mayas Kassabry; Faeda Qtait; Bahaaeddin M. Hammad; Abeer Hussein; Rasmieh Anabtawy; Jamal Qaddumi; Mohammed ALBashtawy; Ola Mousa (BMC Medical Education)
Abstract Background Medical errors are a major concern for patient safety in healthcare institutions globally, making this a critical public health issue leading to significant problems, including increased hospital stays and higher mortality rates. Objectives This study aims to assess nursing students’ awareness of medical errors during their clinical internship. Methods A cross-sectional study was conducted with 280 intern nursing students from the Arab American University in Palestine. A self-administered questionnaire, comprising 43 items across six subscales based on a medical error scale was used to collect data. The analysis was performed using SPSS version 29, with data collected during the Fall of semester 2024. Results The overall mean awareness score was 161 (SD = 75.34) out of a possible 215, with a mean item-level score of 3.74 (on a 5-point scale). Among the subscales, the highest mean score was observed in Care Practices (M = 4.06), while the lowest was in Patient Falls (M = 3.38). Approximately 39.6% of students reported medical errors, with 12.5% involving blood transfusion, 11.4% medication errors, and 20.1% categorized as other errors (e.g., needlestick injuries). The majority (65.7%) reported not committing any errors during their clinical practice. Conclusion The study suggests that intern nursing students have a low tendency to commit medical errors, which bodes well for the implementation of future patient safety protocols. These findings indicate that nursing students are becoming increasingly proficient in safe care practices, thereby reducing medical error rates, and enhancing patient safety in clinical settings. Clinical trial number Not applicable